p53's choice of myocardial death or survival: Oxygen protects infarct myocardium by recruiting p53 on NOS3 promoter through regulation of p53‐Lys118 acetylation - Rajan Gogna; Esha Madan; Mahmood Khan; Uttam Pati; Periannan Kuppusamy (EMBO Molecular Medicine)
Abstract Myocardial infarction, an irreversible cardiac tissue damage, involves progressive loss of cardiomyocytes due to p53‐mediated apoptosis. Oxygenation is known to promote cardiac survival through activation of NOS3 gene. We hypothesized a dual role for p53, which, depending on oxygenation, can elicit apoptotic death signals or NOS3‐mediated survival signals in the infarct heart. p53 exhibited a differential DNA‐binding, namely, BAX‐p53RE in the infarct heart or NOS3‐p53RE in the oxygenated heart, which was regulated by oxygen‐induced, post‐translational modification of p53. In the infarct heart, p53 was heavily acetylated at Lys118 residue, which was exclusively reversed in the oxygenated heart, apparently regulated by oxygen‐dependent expression of TIP60. The inhibition of Lys118 acetylation promoted the generation of NOS3‐promoting prosurvival form of p53. Thus, oxygenation switches p53‐DNA interaction by regulating p53 core‐domain acetylation, promoting a prosurvival transcription activity of p53. Understanding this novel oxygen‐p53 survival pathway will open new avenues in cardioprotection molecular therapy.